Patient and physician views about protocolized dialysis treatment in randomized trials and clinical care. Issue 2 (2nd April 2016) - Kraybill, Ashley; Dember, Laura M.; Joffe, Steven; Karlawish, Jason; Ellenberg, Susan S.; Madden, Vanessa; Halpern, Scott D.
ABSTRACT: Background : Pragmatic trials comparing standard-of-care interventions may improve the quality of care for future patients, but raise ethical questions about limitations on decisional autonomy. We sought to understand how patients and physicians view and respond to these questions in the contexts of pragmatic trials and of usual clinical care.Methods : We conducted scenario-based, semistructured interviews with 32 patients with end-stage renal disease (ESRD) receiving maintenance hemodialysis in outpatient dialysis units and with 24 nephrologists. Each participant was presented with two hypothetical scenarios in which a protocolized approach to hemodialysis treatment time was adopted for the entire dialysis unit as part of a clinical trial or a new clinical practice.Results : A modified grounded theory analysis revealed three major themes: (1) the value of research, (2) the effect of protocolized care on patient and physician autonomy, and (3) information exchange between patients and physicians, including the mechanism of consent. Most patients and physicians were willing to relinquish decisional autonomy and were more willing to relinquish autonomy for research purposes than in clinical care. Patients' concerns toward clinical trials were tempered by their desires for certainty for a positive outcome and for physician validation. Patients tended to believe that being informed about research was more important than the actual mechanism of consent, and most were content with being able to opt out from participating.Conclusions : This qualitative study suggests the general acceptability of a pragmatic clinical trial comparing standard-of-care interventions that limits decisional autonomy for nephrologists and patients receiving hemodialysis. Future studies are needed to determine whether similar findings would emerge among other patients and providers considering other standard-of-care trials.